Penerapan Metode Volleying untuk Meningkatkan Aktivitas dan Keterampilan Passing Atas Bola Voli dengan Media Dinding di SDN Mlokorejo - Bisyafwil Widad Wahyudi; Bahtiar Hari Hardovi; Topo Yono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This classroom action research aims to improve students' activity and upper-pass volleyball skills through the implementation of a wall-based volleying method. In the pre-cycle stage, most students showed low activity levels, indicated by limited understanding of basic techniques, poor movement coordination, and low self-confidence. In Cycle I, the use of the wall as a training medium began to show positive effects, including increased ball-contact frequency, improved coordination, and greater student focus during practice. By Cycle II, students demonstrated significant improvement in activity levels, marked by increased independence during practice, the ability to correct movement errors autonomously, and higher engagement in the learning process. The findings indicate that the wall-based volleying method is effective in enhancing students’ upper-pass technique and improving motivation and active participation in Physical Education learning. Conclusion Based on the results of the research that has been carried out through two cycles, it can be concluded that the application of the volleying method with wall media has a significant impact on increasing the activity and passing skills of students at Mlokorejo Elementary School Keywords: upper pass, volleyball, wall media, learning activity, physical education